Influence of SO2 on the Fuel Conversion Scheme. Implication for Soot Emissions - Abián, María; Millera, Ángela; Bilbao, Rafael; Alzueta, Mª Ujué (Jornada de Jóvenes Investigadores del I3A, 2017)
This work includes an experimental and modeling study of whether sulfur dioxide (SO2), typically present in the recirculated flue gas, can inhibit or promote the overall fuel conversion process in a combustion system, with special attention on SO2 implication for soot emissions and the possible reduction of this pollutant.